Awareness among Students of a Medical College Regarding Management of Animal Bite in Bijapur, Karnataka - SK Shashikantha; MP Sheethal; KJ Shashank (Medsci Publications, 2017)
Introduction: Considering its fatality, any animal bite should be dealt with utmost care. So, it becomes imperative that the health care professionals have appropriate knowledge about the animal bites, risk prevention of Rabies, and be better equipped to tackle this menace more efficiently. This study conducted to assess the level of awareness among students of a medical college regarding management of animal bites Materials and methods: A cross sectional study was conducted during June to July 2015 among 106 final year medical students and interns. Results: Majority of the subjects could correctly classify (Category 1- 62%, Category 2 - 66% and Category 3 - 72.0%) the animal bite wound. With regard to post exposure prophylaxis, only 24% of the study subjects were aware of the correct intradermal schedule and 30% of them were aware of the intramuscular schedule. As a first aid measure after a dog bite, 52% of the subjects were of the opinion that the wound has to be washed with soap and water, 22% opined that secondary suturing should be done after serotherapy and 35% knew that bandaging has to be done only in case of heavy uncontrolled bleeding. Forty six percent of the subjects were aware of the management of category 2 bite wounds. Conclusion: Our study found most of the subjects were aware of the proper categorization of animal bite wound and the prevention of rabies but very few could correctly mention the right schedule of post exposure vaccination to be done